Safety and immunogenicity of a reduced dose of the BNT162b2 mRNA COVID-19 vaccine (REDU-VAC): A single blind, randomized, non-inferiority trial - Pieter Pannus; Stéphanie Depickère; Delphine Kemlin; Sarah Houben; Kristof Y. Neven; Leo Heyndrickx; Johan Michiels; Elisabeth Willems; Stéphane De Craeye; Antoine Francotte; Félicie Chaumont; Véronique Olislagers; et al. (Public Library of Science (PLoS), 2022)
Fractional dosing of COVID-19 vaccines could accelerate vaccination rates in low-income countries. Dose-finding studies of the mRNA vaccine BNT162b2 (Pfizer-BioNTech) suggest that a fractional dose induces comparable antibody responses to the full dose in people <55 years. Here, we report the safety and immunogenicity of a fractional dose regimen of the BNT162b2 vaccine. REDU-VAC is a participant-blinded, randomised, phase 4, non-inferiority study. Adults 18-55 years old, either previously infected or infection naïve, were randomly assigned to receive 20μg/20μg (fractional dose) or 30μg/30μg (full dose) of BNT162b2. The primary endpoint was the geometric mean ratio (GMR) of SARS-CoV-2 anti-RBD IgG titres at 28 days post second dose between the reduced and full dose regimens. The reduced dose was considered non-inferior to the full dose if the lower limit of the two-sided 95% CI of the GMR was >0.67. Primary analysis was done on the per-protocol population, including infection naïve participants only. 145 participants were enrolled and randomized, were mostly female (69.5%), of European origin (95%), with a mean age of 40.4 years (SD 7.9). At 28 days post second dose, the geometric mean titre (GMT) of anti-RBD IgG of the reduced dose regimen (1,705 BAU/mL) was not non-inferior to the full dose regimen (2,387 BAU/mL), with a GMR of 0.714 (two-sided 95% CI 0.540-0.944). No serious adverse events occurred. While non-inferiority of the reduced dose regimen was not demonstrated, the anti-RBD IgG titre was only moderately lower than that of the full dose regimen and, importantly, still markedly higher than the reported antibody response to the licensed adenoviral vector vaccines. These data suggest that reduced doses of the BNT162b2 mRNA vaccine may offer additional benefit as compared to the vaccines currently in use in most low and middle-income countries, warranting larger immunogenicity and effectiveness trials. Trial Registration: The trial is registered at ClinicalTrials.gov (NCT04852861).